Sensory Play in Early Childhood Education: The Key to Stimulating the Brain and Creativity of Young Children - Arjulayana Arjulayana (Journal of Gemilang, 2025)
Sensory play has become a foundational component in early childhood education because it stimulates neural development, creativity, emotional regulation, and fine motor control through direct multisensory engagement. This study employs a systematic literature review of 34 peer-reviewed publications to synthesize evidence on how sensory play promotes brain activation and creative capacities in young children. The findings demonstrate that tactile experiences, movement-based sensory activities, symbolic and dramatic play, and structured multisensory learning tools consistently strengthen cognitive functioning, emotional stability, imagination, and motor coordination. Sustainability requires alignment among teachers, school leadership, parents, and communities to institutionalize sensory play as a long-term pedagogical priority rather than a supplementary activity. This study contributes by mapping the mechanisms, learning components, and sustainability requirements that enable sensory play to function as a holistic developmental framework in early childhood education